Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1998
DOI: 10.1115/98-gt-173
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Flowfield Measurements in the Leading Edge Region of a Stator Vane Endwall

Abstract: The leading edge region of a first stage stator vane experiences high heat transfer rates especially near the end wall making it very important to get a better understanding of the formation of the leading edge vortex. In order to improve numerical predictions of the complex endwall flow, benchmark quality experimental data are required. To this purpose, this study documents the endwall heat transfer and static pressure coefficient distribution of a modern stator vane for two different exit Reynolds numbers (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Several efforts were made previously to understand the contributions of high freestream Tu and Re on timeaveraged endwall heat transfer in gas turbine vanes ( [15], [16]). Blair [12] and Dunn et al [13] were among the initial researchers who investigated the endwall heat flux rates between turbine cascade blades and reported an increase by a factor of 3 near the leading edge of endwall and turbine junction.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several efforts were made previously to understand the contributions of high freestream Tu and Re on timeaveraged endwall heat transfer in gas turbine vanes ( [15], [16]). Blair [12] and Dunn et al [13] were among the initial researchers who investigated the endwall heat flux rates between turbine cascade blades and reported an increase by a factor of 3 near the leading edge of endwall and turbine junction.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Radomsky and Thole [15] introduced T a freestream turbulence of 20% and found a 15% increase in endwall heat transfer underneath the horseshoe vortex core. Kang et al [16] reported that secondary flows contributed to the increase of the trailing edge endwall heat transfer of a vane. Ames et al [17] furthered the research efforts of understanding vane endwall heat transfer by introducing a mock aeroderivative combustion system upstream of a turbine vane cascade, where turbulence levels ranged from 0.7% to 14% and inlet Reynolds numbers based on true chord length and exit conditions were as high as 2,000,000.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The heat flux plates, depicted in Figure 2a, were manufactured in three sections, where the center section around the blades could be removed to install the flat or the contoured endwalls. For both endwall types, the heat flux plates consisted of serpentine inconel circuits encapsulated in kapton for a total thickness of 75 µm, with a 37 µm copper layer adhered to the top surface to increase heat flux uniformity (Kang et al [24]). The copper was painted with flat black paint to increase emissivity for infrared camera measurements.…”
Section: Endwall Heat Transfer Measurementsmentioning
confidence: 99%
“…The stator vane geometry was a twodimensional slice of an engine profile taken at the vane midspan. The construction and the development of the scaled-up stator turbine vane and the test section have been previously documented by Radomsky and Thole (1998) and Kang, et al (1998). The wind tunnel used in this study is recirculating with a corner test section, shown in Figure 1.…”
Section: Experimental Facility and Instrumentationmentioning
confidence: 99%